2015
DOI: 10.1007/s11095-015-1700-8
|View full text |Cite
|
Sign up to set email alerts
|

Microsphere-Based Rapamycin Delivery, Systemic Versus Local Administration in a Rat Model of Renal Ischemia/Reperfusion Injury

Abstract: PurposeThe increasing prevalence and treatment costs of kidney diseases call for innovative therapeutic strategies that prevent disease progression at an early stage. We studied a novel method of subcapsular injection of monodisperse microspheres, to use as a local delivery system of drugs to the kidney.MethodsWe generated placebo- and rapamycin monodisperse microspheres to investigate subcapsular delivery of drugs. Using a rat model of acute kidney injury, subcapsular injection of placebo and rapamycin monodi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…Ischemia and reperfusion (I/R) injury, a common and major cause of acute kidney injury and renal failure, is closely associated with various clinical procedures and conditions, such as kidney grafting and hypovolemic shock (1)(2)(3). However, with the increasing prevalence of allograft renal transplantation, graft renal function and allograft survival are significantly affected by I/R injury, which remains poorly understood and ameliorated (4). After transitory, warm ischemia, before and during donor kidney removal, and cold ischemia, during organ transportation, preservation, and repair, reperfusion has a substantial role in amplifying ischemic renal injury.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Ischemia and reperfusion (I/R) injury, a common and major cause of acute kidney injury and renal failure, is closely associated with various clinical procedures and conditions, such as kidney grafting and hypovolemic shock (1)(2)(3). However, with the increasing prevalence of allograft renal transplantation, graft renal function and allograft survival are significantly affected by I/R injury, which remains poorly understood and ameliorated (4). After transitory, warm ischemia, before and during donor kidney removal, and cold ischemia, during organ transportation, preservation, and repair, reperfusion has a substantial role in amplifying ischemic renal injury.…”
mentioning
confidence: 99%
“…Nevertheless, to date, controversy remains regarding whether autophagy is the primary mechanism participating in the regulatory effect of rapamycin in renal I/R injury and what role rapamycin or autophagy has in response to stressors. Some studies focusing on rapamycin or autophagy have suggested a protective role against graft rejection and in renal protection (6,16,17); however, other reports have conversely indicated that administrating rapamycin or inducing autophagy increased nephrotoxicity and remarkably prolonged graft recovery (4,(18)(19)(20). Importantly, Gonçalves et al (21) and Jiang et al (17) demonstrated contradictory functions of rapamycin in renal I/R injury with long administration and reperfusion times.…”
mentioning
confidence: 99%
“…AKI is mainly caused by sepsis, ischemia-reperfusion, and/or nephrotoxicity, and it is characterized by rapid progression of inflammation and oxidative stress. Different drug delivery systems have recently been explored for AKI therapy in murine models, including drug conjugates [ 304 ], micelles [ 305 ], nanoparticles [ 306 ], microspheres [ 307 ], and injectable hydrogels [ 308 ]. Of note, Ji and Du et al designed pH-responsive and AKI-kidney targeting nanopolyplexes by electrostatic forces between anionic hyaluronic acid and cationic chitosan for effective delivery of SS-31 (a mitochondrial targeting peptide with potent antioxidant activity) to treat AKI.…”
Section: Treatment Of Inflammatory Diseases By Bioresponsive Drug Delmentioning
confidence: 99%
“…Temporary blocking of renal blood flow is required in some complex renal surgeries, such as renal parenchymal lithotomy, renal transplantation and renal tumor resection. Postoperative reperfusion may lead to increased injury of ische mic renal tissue, which is called renal ischemia-reperfusion injury (RIRI) ( 1 ). RIRI can lead to renal failure and acute renal insufficiency, causing high morbidity and mortality.…”
Section: Introductionmentioning
confidence: 99%